(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Purpose: Age-related cataract is one of the leading causes of blindness and avoidable visual impairment in the world. There is no time-tested, FDA-approved, or clinically proven medical treatment exists till date to delay, prevent, or reverse the progression of senile cataract. Nirgundi (Vitex negundo) is a Chakshushya single drug mentioned in Ayurvedic classics. Various animal experimental study and invitro studies in recent years using flavonoids extracted from leaves of Vitex negundo on selenite induced cataract models proved to be beneficial in arresting the progression of cataract. Hence a clinical study with Vitex negundo eye drops in the form of Arka was planned with primary objective to assess the effect of Nirgundi patra arka as Aschotana (eye drops) in pre senile cataract. Methods: The study design was interventional pre and post evaluation without control. Patients were advised to instill Nirgundi patra arka two drops thrice daily i.e. 6 am, 12 pm and 6pm for a period of 6months. Log mar visual acuity score and contrast sensitivity score were recorded before treatment, 3rd month of treatment, after treatment, 9th month (1st follow up) and 12th month (2nd follow up). Slit lamp photographs were recorded before treatment and 12th month. Study and follow up were done in 31 eyes. Result: The intervention is statistically significant while considering visual acuity and contrast sensitivity. All the 27 cases of nuclear cataract responded to the intervention, while only 83.3% of posterior sub capsular cataract and 60% of cortical cataract showed response. But the change was not significant statistically. Conclusion: The intervention was effective in improving visual acuity and contrast sensitivity in all types of pre senile cataract. Clinical assessment revealed the study was effective in preventing the progression of pathogenesis in early stage of nuclear cataract.